The Poet Of Dreams - Gable, Sal (Cornfield Review, 2016)
Margaret Marie Janviev is a 26-year-old writer who is very fond of her poetry. Her best friend is Chloe who she hangs out on a rainy night at a local café. As she begins walking home from the local café, she decides to take a detour where she will meet her lovely sweet escape. Once she's there enjoying herself, someone or something meets with her and a deeper meaning lays within than what meets the eye.